La Candelaria Ridge (NW Argentina) as a natural lab for the exploration of the geothermal system of Rosario de La Frontera: Methods and preliminary results - Maffucci, R. (2012)
Within the scientific framework recently proposed by C.U.I.A. (Consorzio Universitario Italiano per l’Argentina) for the development of applied researches on the Argentina territory, several research groups, belonging to selected Italian and Argentina Universities, converged in the last year on the research line devoted to the “Sustainable development of future towns”. This contribution focuses on the preliminary results achieved by this collaboration among the Universities of Camerino, Jujuy, Roma Tre, Salta, Sapienza. The project focuses on the application of robust methodologies and the development of new ones to explore the geothermal potential of the area of Rosario de La Frontera (NW Argentina) located at the northern edge of La Candelaria Ridge, one of positively inverted structures cropping out between the provinces of Salta and Tucuman. It belongs to the Santa Barbara System of the Andes retro-wedge...